Preparation method and application of in-situ hydroxylation organic silicon composite film
The thiol-ene click reaction introduces hydrophilic groups under green and safe conditions to form an in-situ hydroxylated silicone material and combines with graphene oxide nanosheets, which solves the problem of harsh reaction conditions in the prior art. Improve the permeability and separation performance of the silicone film.
Patent Information
- Application Number
- CN202411589190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, the modification reaction conditions of bridged silicone are harsh, and there are problems of safety and long cycles, making it difficult to effectively improve the permeability and separation performance of the silicone film.
The thiol-ene click reaction is carried out under green and safe conditions. The carbon-carbon double bond reacts with the thiol group by ultraviolet lamp irradiation initiator, and the hydrophilic groups are quickly introduced to form in situ hydroxylated organic silicon. The composite film was prepared by ultrasonic spraying.
It achieves a high-purity in-situ hydroxylated silicone composite film at room temperature, which improves the water permeability and separation performance of the film, forms a dense silicon network structure, and enhances the separation performance.
Smart Images

Figure HDA0005125104790000011 
Figure HDA0005125104790000012 
Figure HDA0005125104790000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of modified organosilicon preparation, and specifically relates to a preparation method and application of an in-situ hydroxylated organosilicon composite film. Background Art
[0002] Bridged silicone has great potential in the field of membrane separation due to its good hydrothermal stability and chemical stability, as well as excellent molecular sieving ability. In addition, due to the different groups contained in R in its structure ([R-Si-O-R']n), it has good processing ability. For example, the structure of 1,2-bis(triethoxysilyl)ethylene (BTESEthy) contains a rigid and highly polar vinylidene bridge structure (C=C), which has high chemical reactivity and can be further modified to improve the permeation separation performance of silicone membranes.
[0003] Patent ZL 201910301859.9 proposes to use chlorosulfonic acid to modify aromatic bridged silicone to improve its hydrophilicity and adjust its pore structure, but the reaction involves concentrated hydrochloric acid and low temperature conditions, which leads to problems such as safety and long cycle in the process. Therefore, we use the thiol-ene click reaction, which has mild reaction conditions, fast reaction speed, and high selectivity. The reaction only requires ultraviolet light irradiation and initiators to make the carbon-carbon double bond (C=C) react with the thiol (-SH), thereby quickly introducing hydrophilic groups into the BTESEthy structure, effectively solving the problems of harsh reaction conditions and long time. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention proposes a method for preparing an in-situ hydroxylated organic silicon composite film, and an in-situ hydroxylated organic silicon material can be quickly obtained by performing a mercapto-ene click reaction under green and safe conditions.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing an in-situ hydroxylated organic silicon composite film, characterized in that: it comprises:
[0006] As a preferred embodiment of the preparation method of the present invention, wherein:
[0007] (1) A quartz reaction bottle is filled with nitrogen, and dithiothreitol (DTT) and a photoinitiator are added. A small amount of ethanol is added until they are completely dissolved, and then an organosilicon precursor 1,2-bis(triethoxysilyl)ethylene (BTESEthy) is added. The reaction bottle is placed in a light-shielding environment, irradiated with an ultraviolet lamp, and stirred for a period of time to obtain an in-situ hydroxylated organosilicon precursor.
[0008] (2) The in-situ hydroxylated organosilicon precursor is vacuum dried at a certain temperature, washed with an organic solvent to remove the initiator and unreacted DTT, and then dried to remove the organic solvent. A certain amount of ethanol, ammonia water, and deionized water are added, and stirred in a water bath at a certain temperature for a period of time to obtain an in-situ hydroxylated organosilicon sol.
[0009] (3) The in-situ hydroxylated organosilicon sol is diluted to a certain concentration and then coated on a PVDF polymer membrane loaded with graphene oxide nanosheets (GO). After calcination for a period of time, an in-situ hydroxylated organosilicon composite membrane is obtained.
[0010] The coating method includes but is not limited to spraying, spin coating, dipping, etc.; preferably, the present invention adopts an ultrasonic physicochemical spraying method for coating.
[0011] The molar ratio of BTESEthy, DTT and photoinitiator is 1:0.2-10:0.1-0.5. As a preferred embodiment of the preparation method of the present invention, the molar ratio of the vinyl bridged organosilicon material BTESEthy and the in-situ hydroxylation agent DTT is 1:1.
[0012] As a preferred embodiment of the preparation method of the present invention, the power of the ultraviolet lamp is 30-100W, the wavelength is 320-400nm, and the irradiation time is 0.5-24h.
[0013] As a preferred embodiment of the preparation method of the present invention, the alcohol solvent is methanol, ethanol, isopropanol, n-propanol or n-butanol.
[0014] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the hybrid organic silicon material, ammonia water and deionized water is 1:0.1-0.6:30-120.
[0015] As a preferred embodiment of the preparation method of the present invention, the in-situ hydroxylated organic silicon sol is coated on the GO layer of the PVDF membrane by ultrasonic atomization spraying, wherein the concentration of the coated in-situ hydroxylated organic silicon sol is 0.1-10wt%.
[0016] As a preferred embodiment of the preparation method of the present invention, the calcination temperature is 60 to 120° C. and the calcination time is 15 to 60 minutes.
[0017] The higher the calcination temperature, the denser the silicone layer. The minimum temperature is 60°C. When the calcination temperature is greater than 80°C, the substrate PVDF deforms. When the calcination temperature is greater than 120°C, the substrate undergoes irreversible deformation.
[0018] The prepared in-situ hydroxylated organic silicon composite membrane is used as a permeation separation membrane in the active blue / water system.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention uses a commercially available low-power ultraviolet lamp to obtain in-situ hydroxylated silicone by a short reaction time at room temperature. The reaction is safe, green and rapid. Due to its high selectivity, high-purity in-situ hydroxylated silicone can be obtained.
[0021] (2) The DTT structure used contains two thiol groups, which provides more possibilities for the reaction, thereby introducing more hydrophilic groups, and C-OH can undergo condensation reaction with Si-OH to generate a denser silicon network structure, which can enhance the separation performance on the basis of providing hydrophilicity. The present invention introduces a hydrophilic hydroxyl group by chemically reacting C=C with -SH, and generates a strong CS chemical bond that is difficult to decompose. The newly introduced hydroxyl group can also participate in the dehydration condensation process in the subsequent sol preparation process, thereby improving the water permeability and separation performance of the prepared organic silicon composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0023] Figure 1 Schematic diagram of the modification process of the organosilicon material through the click reaction in Example 1 of the present invention.
[0024] Figure 2 (1) is a schematic diagram of the dehydration condensation reaction in the preparation of the sol of Example 1 of the present invention, and (2) is a schematic diagram of the hydrolysis condensation reaction of DTT.
[0025] Figure 3 The infrared spectra of the silicone before and after modification of Example 1 of the present invention are as follows DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] The raw materials used in the present invention are commercially available unless otherwise specified.
[0030] Table 1
[0031] name Commercial channels Part Number Dithiothreitol Myrelle M32594 2-Benzyl-2-(dimethylamino)-4'-morpholinophenylbutanone Myrelle M54856 Benzoin dimethyl ether Maclean B802287 1,2-Bis(triethoxysilyl)ethylene Myrelle GEL-SIB1820.0
[0032] Example 1
[0033] The present invention provides a method for preparing an amino acid-modified organic silicon composite film:
[0034] (1) Nitrogen was introduced into a quartz tube for 20 min, 0.155 g DTT, 0.0254 g benzoin dimethyl ether (DMPA), 0.353 g BTESEthy, and then 3 mL of anhydrous ethanol was added until they were completely dissolved. After nitrogen was introduced for 20 min, the tube was sealed and then placed in a light-shielding environment and irradiated with 40 W 365 nm ultraviolet light and stirred for 3 h to obtain an in situ hydroxylated organosilicon precursor (BTESEthy-DTT).
[0035] (2) Dissolve BTESEthy-DTT in anhydrous ethanol, add deionized water and 10% ammonia water (molar ratio of BTESEthy-DTT:H2O:10% ammonia water=1:60:0.2), and stir in a water bath at 50°C for 2 h to prepare a 5 wt% organosilica sol.
[0036] (3) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0037] (4) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step size 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, coat it on the transition layer preheated at 30°C, then calcine at 80°C for 30 min, and repeat step (4) twice to form an organosilicon layer with a thickness of about 100 nm, thereby obtaining an in-situ hydroxylated organosilicon polymer composite film.
[0038] Comparative Example 1
[0039] The difference from Example 1 is that unmodified BTESEthy is used to prepare the organic silicon composite film.
[0040] (1) Dissolve BTESEthy in anhydrous ethanol, add deionized water and 10% ammonia water (molar ratio of BTESEthy:H2O:10% ammonia water=1:60:0.2), and stir in a water bath at 50°C for 2 h to prepare a 5 wt% organosilica sol.
[0041] (2) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0042] (3) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step size 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, apply it on the transition layer preheated at 30°C, then calcine at 80°C for 30 min, and repeat step (4) twice to form an organosilicon layer with a thickness of about 100 nm to obtain an organosilicon polymer composite film.
[0043] Comparative Example 2
[0044] The difference from Example 1 is that there is no ultraviolet light condition in step (1).
[0045] (1) Nitrogen was introduced into a quartz tube for 20 min. 0.155 g DTT, 0.0254 g DMPA, and 0.353 g BTESEthy were added, and then 3 mL of anhydrous ethanol was added until they were completely dissolved. After nitrogen was introduced for 20 min, the tube was sealed and then placed in a light-shielded environment and stirred for 3 h.
[0046] (2) Dissolve BTESEthy-DTT in anhydrous ethanol, add deionized water and 10% ammonia water (molar ratio of BTESEthy-DTT:H2O:10% ammonia water=1:60:0.2), and stir in a water bath at 50°C for 2 h to prepare a 5 wt% organosilica sol.
[0047] (3) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0048] (4) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step size 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, coat it on the transition layer preheated at 30°C, then calcine at 80°C for 30 min, and repeat step (4) twice to form an organosilicon layer with a thickness of about 100 nm to obtain an organosilicon polymer composite film.
[0049] Comparative Example 3
[0050] The difference from Example 1 is that there is no click reaction under DTT in step (1).
[0051] (1) Nitrogen was introduced into a quartz tube for 20 min, 0.0254 g DMPA, 0.353 g BTESEthy, and then 3 mL of anhydrous ethanol were added until they were completely dissolved. After nitrogen was introduced for 20 min, the tube was sealed and then placed in a light-shielding environment and irradiated with 40 W 365 nm ultraviolet light for 3 h.
[0052] (2) Dissolve BTESEthy in anhydrous ethanol, add deionized water and 10% ammonia water (molar ratio of BTESEthy:H2O:10% ammonia water=1:60:0.2), and stir in a water bath at 50°C for 2 h to obtain a 5 wt% organosilica sol.
[0053] (3) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0054] (4) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step size 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, coat it on the transition layer preheated at 30°C, then calcine at 80°C for 30 min, and repeat step (4) twice to form an organosilicon layer with a thickness of about 100 nm to obtain an organosilicon polymer composite film.
[0055] Comparative Example 4
[0056] The difference from Example 1 is that chlorosulfonic acid is used instead of DTT as the modifying material.
[0057] (1) Under low temperature conditions, chlorosulfonic acid was dissolved in dichloromethane, and then BTESEthy was added for low temperature sulfonation reaction (wherein the molar ratio of chlorosulfonic acid to BTESEthy was 1:1), and the reaction was stirred for 30 minutes. Then the beaker was transferred to a 30°C water bath, stirred for 48 hours, and then an appropriate amount of concentrated hydrochloric acid was added to precipitate the sulfonic acid functionalized modified silicone precursor.
[0058] (2) The sulfonic acid modified organosilicon precursor prepared in step (1) was dissolved in ethanol, deionized water and 3.7 wt% hydrochloric acid were added, and the mixture was stirred continuously for 2 h in a water bath at 40° C. to obtain a sulfonic acid modified organosilicon sol, wherein the molar ratio of the sulfonic acid organosilicon precursor, water, and hydrochloric acid was 1:60:0.2.
[0059] (3) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0060] (4) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step distance 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, coat it on the preheated transition layer, and then calcine it at 80°C for 30 min, and repeat step (4) twice to obtain a sulfonated organosilicon polymer composite membrane.
[0061] Comparative Example 5
[0062] The difference from Example 1 is that thiomalic acid (MSA) is used as the modification material instead of DTT.
[0063] (1) Nitrogen was introduced into a quartz tube for 20 min, 0.150 g MSA, 0.0251 g DMPA, 0.353 g BTESEthy, and then 3 mL of anhydrous ethanol were added until they were completely dissolved. After nitrogen was introduced for 20 min, the tube was sealed and then placed in a light-shielding environment and irradiated with 40 W 365 nm ultraviolet light and stirred for 3 h to obtain an in situ hydroxylated organosilicon precursor (BTESEthy-MSA).
[0064] (2) BTESEthy-MSA was dissolved in anhydrous ethanol, deionized water and 10% ammonia water (molar ratio of BTESEthy-MSA:H2O:10% ammonia water = 1:60:0.2) were added, and stirred in a water bath at 50°C for 2 h to obtain a 5 wt% organosilica sol.
[0065] (3) 30 mL of 0.1 wt% GO nanosheet solution was loaded on the surface of PVDF (molecular weight cutoff 100000 Da) polymer membrane by suction filtration and placed in an oven for vacuum drying at 60 °C for 1 h to obtain a nanosheet with an effective area of 12.56 cm 2 GO nanosheet transition layer.
[0066] (4) Pre-set the parameters of the ultrasonic atomization sprayer (air pressure 0.003 MPa, feed liquid flow rate 0.1 mL / min, step size 1 mm), then dilute the sol to 3 wt% and add it to the sprayer, apply it on the transition layer preheated at 30°C, then calcine at 80°C for 30 min, and repeat step (4) twice to form an organosilicon layer with a thickness of about 100 nm to obtain a carboxylated organosilicon polymer composite film.
[0067] The sulfonic acid functionalized modified organic silicon composite membranes prepared in Example 1 and Comparative Examples 1 to 5 were applied to a 100 ppm reactive blue 19 (RB 19) / water separation system at 0.4 MPa (4 bar).
[0068] Table 1
[0069] <![CDATA[Water permeability L / (m 2 ·h·bar)]]> Retention rate (%) Example 1 2.96 97.7 Comparative Example 1 1.41 88.6 Comparative Example 2 1.89 91.3 Comparative Example 3 1.37 89.1 Comparative Example 4 2.08 93.7 Comparative Example 5 2.35 92.8
[0070] Compared with Comparative Example 1, Example 1 introduces a hydrophilic group -OH into the BTESEthy structure through a click reaction, thereby improving the hydrophilicity of the modified organosilicon, improving the water permeability of the membrane, and the steric hindrance of BTESEthy-DTT is greater, and a denser network structure can be formed, thereby increasing the interception rate; in Comparative Example 2, there is no ultraviolet light illumination condition, and the click reaction cannot be triggered, and BTESEthy-DTT is formed in the subsequent hydrolysis and condensation process, but the Si-OC structure is not stable and decomposes in the aqueous solution of the test system, resulting in the separation and permeability of the membrane being not significantly improved; in Comparative Example 3, there is no DTT combined with BTESEthy, and ultraviolet light and initiators have almost no effect on BTESEthy, and its separation and permeability performance are not significantly different from those of unmodified BTESEthy. In Comparative Example 4, BTESEthy is modified by chlorosulfonic acid under low temperature conditions, and the required reaction time is relatively long, and chlorosulfonic acid cannot be well introduced into the BTESEthy structure, resulting in the final composite membrane separation and permeability performance improvement is not as good as BTESEthy-DTT. Comparative Example 5 also uses a click reaction. The difference from Example 1 is that a carboxyl group is introduced to improve hydrophilicity. The DTT structure contains two thiol groups, which provide more possibilities for the reaction, thereby introducing more hydrophilic groups, and C-OH can undergo a condensation reaction with Si-OH to generate a denser silicon network structure, which can enhance the separation performance on the basis of providing hydrophilicity.
[0071] Figure 1 For the technical route of the present invention, Figure 2 (1) Schematic diagram of the network structure formed by the organosilicon precursor, and (2) Schematic diagram of the densification of the organosilicon network by DTT. Figure 3 The infrared spectra of BTESEthy and BTESEthy-DTT are shown in Figure 3, where 3700-3000 cm -1 The -OH peak at 2500cm is the peak of bound water and BTESEthy (or BTESEthy-DTT) structure. Since BTESEthy structure is relatively loose and contains more bound water, its -OH peak intensity is higher, 2500cm -1 The left and right are the -SH peaks in the BTESEthy-DTT structure, 1650 cm -1 The left and right are C=C peaks. After the click reaction, C=C in BTESEthy-DTT disappeared, indicating that the click reaction was successful. -1 The decrease in the intensity of the CH peak on the C=C at the left and right also indicates that the click reaction occurs, 900 cm -1 It is the Si-OH peak. After the Si-OH in BTESEthy-DTT reacts with C-OH, the peak is weakened. The formed Si-OC makes the BTESEthy-DTT structure more compact.
[0072] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing an in-situ hydroxylated organic silicon composite film, characterized in that: include, (1) introducing N2 into a reaction device, adding anhydrous ethanol, then dissolving dithiothreitol, a photoinitiator, and 1,2-bis(triethoxysilyl)ethylene in the anhydrous ethanol, and irradiating the reaction with an ultraviolet lamp under a light-shielding environment to obtain an in-situ hydroxylated organosilicon precursor; (2) dissolving the in-situ hydroxylated organosilicon precursor in anhydrous ethanol, adding deionized water and ammonia water, and stirring in a water bath to obtain an in-situ hydroxylated silica sol; (3) The in-situ hydroxylated organic silicon sol prepared above is diluted with anhydrous ethanol to different concentrations, coated on a PVDF membrane loaded with graphene oxide nanosheets, and calcined in an oven to obtain an in-situ hydroxylated organic silicon composite membrane.
2. The preparation method according to claim 1, characterized in that: The molar ratio of 1,2-bis(triethoxysilyl)ethylene, dithiothreitol and photoinitiator is 1:0.2-10:0.1-0.
5.
3. The preparation method according to claim 1, characterized in that: The photoinitiator is one of 2-benzyl-2-(dimethylamino)-4'-morpholinyl phenyl butanone and benzoin dimethyl ether.
4. The preparation method according to claim 1, characterized in that: The specifications of the ultraviolet lamp used are: wavelength 320-400nm, power 30-100W; ultraviolet lamp irradiation reaction time is 0.5-24h.
5. The preparation method according to claim 1, characterized in that: The molar ratio of the in-situ hydroxylated organosilicon precursor, ammonia water and deionized water is 1:0.1-0.6:30-120.
6. The preparation method according to claim 1, characterized in that: The stirring condition of the water bath is 50-60°C for 1-3 hours.
7. The preparation method according to claim 1, characterized in that: The coating method is one of spray coating, spin coating and dipping, and the concentration of the sol used for coating is 0.1-10wt%.
8. The preparation method according to claim 1, characterized in that: The calcination temperature is 60-120° C., and the calcination time is 15-60 minutes.
9. Use of the in-situ hydroxylated organic silicon composite membrane prepared by the method according to any one of claims 1 to 8 as a permeation separation membrane.
10. Use of the in-situ hydroxylated organic silicon composite membrane prepared by the method according to any one of claims 1 to 8 as a permeation separation membrane in a reactive blue / water system.
Citation Information
Patent Citations
A method for preparing and applying an aromatic bridged organosilicon hybrid membrane with sulfonic acid functionalization modification.
CN109925897B
Preparation methd of sulfonic group functionalized modified organic silica sol and nanofiltration body
CN113024813A
Preparation method and application of sulfo group functionalization modified organic silicon composite film
CN118594296A
Preparation method and application of GO / organosilicon composite nanofiltration membrane
CN118788156A
Protein-proteophore complexes
US20070020224A1